(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
Nowadays, the regulation and the institutional system of the general educational and vocational teacher training are different in Hungary. The beginning of this historical tradition, and the separation of the two teacher training systems is demonstrated in this study. In the middle of the 19th century, teacher training institutions were established in the dualistic Hungary by a politician of education, baron József Eötvös. The general educational teacher training was established at the University of Pest, the vocational teachers studied at the Technical University. Successor of Eötvös, Augustine Trefort united the two institutions in the summer of 1873, and linked them with the Faculty of Humanities at the University of Pest. This action temporarily ceased the institutional separation of the two teacher trainings. In 1898 the vocational teacher training became independent again: The State Trade School Teacher Training Institute was established.